The moderating role of organizational culture on the effect of organizational justice on organizational citizenship behavior - Ira Mardiyanti; Suharnomo Suharnomo (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
The main objective of this study is to examine the effect of distributive justice and procedural justice on organizational citizenship behavior (OCB) with organizational culture as a moderating variable. The data in this study were collected from questionnaires distributed to 94 permanent employees of PT Telekomunikasi Indonesia (Telkom) Tbk. Regional Division IV. Hypotheses testing shows that distributive and procedural justice positively affects OCB. Organizational culture is also found to be the moderator on the effect of procedural justice on OCB. However, our prediction that organizational culture could be the moderator on the effect of distributive justice on OCB is not supported. Further results and discussion are explained.